Linguistic Marginalization - Understanding the Process and Effects on Developmental Capabilities - Recordings and translations (English) of interviews in Swahili - Rosendal, Tove (University of Gothenburg, 2020)
The project is a sociolinguistic study that investigates language use from a development perspective, with a central aim of identifying the reasons behind code-switching, i.e. the alternation between Ngoni and Swahili, in the Ruvuma Region in southwestern Tanzania. In a language contact situation with the high status official language Swahili, a main question is if the Ngoni people no longer can express themselves adequately in Ngoni, - that is if the alternation between the two languages is used to fill linguistic gaps and achieving discursive aims, or if it expresses the shaping of identity.

In the recordings rural Ngoni farmers voice their ideas about their cultural heritage, with a special focus on attitudes towards Ngoni culture and cultural changes. The recordings deal with value systems, rituals, taboos and traditions, and naming traditions.

The data consists of 36 sound recordings in Ngoni with totally 27 informants/participants who are all bilingual in Ngoni and Swahili. The participants live in two villages outside Songea in the Ruvuma Region of Tanzania, Mhepai and Peramiho B. The sound recordings are 9 focus group recordings and 27 interviews with the participants of the focus group discussions. All participants have given their consent.

The focus group recordings are totally about 6 hours. The 9 focus groups were: 15 young persons between 15–20 years old (6 boys and 3 girls from Peramiho B and 3 boys and 3 girls from Mhepai), and 12 persons above the age of 60 (3 women and 3 men from Peramiho B and 3 women and 3 men from Mhepai).
All focus group recordings are transcribed and translated into Swahili and English. Code switching to Swahili is marked in bold, even in transcriptions and translations. The interviews were conducted in Swahili, sometimes with parts in ngoni, if needed. The English translations of the interviews are found in the data set, as well as the recordings in Swahili.

Each participant has additionally been interviewed after the focus group recording. The qualitative interviews with the 27 informants between the ages of 18 and 77 (13 hours of recordings in total) were conducted in Swahili by the researcher and a Tanzanian assistant. The recordings were conducted in August- September 2014.

A metadata sheet with anonymised participants is attached. The metadata consists among other of age, sex, educational level and profession. Additionally, information about the participants' bilingualism, as well as their self-estimation of proficiency in Swahili is given.

Background information about the area and participants:
The Ngoni speaking area is situated between Tanzania’s Mozambican border and
Lake Nyasa, around 1000 km from Dar es Salaam. See map. The area is rather isolated with poor roads. The village of Peramiho B is bigger and more urban than Mhepai, which is remote with hardly any vehicles for transport. Although Peramiho B has a more central and urban location, the living conditions in both villages are similar. People have no electricity, except for an occasional solar panel, and people living in the area are typically subsistence farmers growing maize and other crops. The informants were all farmers, except for 6 young people, from Peramiho B (2 motorcyclists transporting people, 2 masons, I technician and 1 nurse). This lifestyle in the villages implies hard work six days a week. People go to their farming plots in the morning and return at sundown. The villages only have some market stalls and outdoor bars where villagers meet to chat and drink local beer.

Purpose:

The project is a sociolinguistic study that investigates language use from a development perspective, with a central aim of identifying the reasons behind code-switching, i.e. the alternation between Ngoni and Swahili, in the Ruvuma Region in southwestern Tanzania. In a language contact situation with the high status official language Swahili, a main question is if the Ngoni people no longer can express themselves adequately in Ngoni, - that is if the alternation between the two languages is used to fill linguistic gaps and achieving discursive aims, or if it expresses the shaping of identity.

In the recordings rural Ngoni farmers voice their ideas about their cultural heritage, with a special focus on attitudes towards Ngoni culture and cultural changes. The recordings deal with value systems, rituals, taboos and traditions, and naming traditions.

The data consists of 36 sound recordings in Ngoni with totally 27 informants/participants who are all bilingual in Ngoni and Swahili. The participants live in two villages outside Songea in the Ruvuma Region of Tanzania, Mhepai and Peramiho B. The sound recordings are 9 focus group recordings and 27 interviews with the participants of the focus group discussions. All participants have given their consent.

The focus group recordings are totally about 6 hours. The 9 focus groups were: 15 young persons between 15–20 years old (6 boys and 3 girls from Peramiho B and 3 boys and 3 girls from Mhepai), and 12 persons above the age of 60 (3 women and 3 men from Peramiho B and 3 women and 3 men from Mhepai).
All focus group recordings are transcribed and translated into Swahili and English. Code switching to Swahili is marked in bold, even in transcriptions and translations. The interviews were conducted in Swahili, sometimes with parts in ngoni, if needed. The English translations of the interviews are found in the data set, as well as the recordings in Swahili.

Each participant has additionally been interviewed after the focus group recording. The qualitative interviews with the 27 informants between the ages of 18 and 77 (13 hours of recordings in total) were conducted in Swahili by the researcher and a Tanzanian assistant. The recordings were conducted in August- September 2014.

A metadata sheet with anonymised participants is attached. The metadata consists among other of age, sex, educational level and profession. Additionally, information about the participants' bilingualism, as well as their self-estimation of proficiency in Swahili is given.

Background information about the area and participants:
The Ngoni speaking area is situated between Tanzania’s Mozambican border and
Lake Nyasa, around 1000 km from Dar es Salaam. See map. The area is rather isolated with poor roads. The village of Peramiho B is bigger and more urban than Mhepai, which is remote with hardly any vehicles for transport. Although Peramiho B has a more central and urban location, the living conditions in both villages are similar. People have no electricity, except for an occasional solar panel, and people living in the area are typically subsistence farmers growing maize and other crops. The informants were all farmers, except for 6 young people, from Peramiho B (2 motorcyclists transporting people, 2 masons, I technician and 1 nurse). This lifestyle in the villages implies hard work six days a week. People go to their farming plots in the morning and return at sundown. The villages only have some market stalls and outdoor bars where villagers meet to chat and drink local beer.

Transcriptions of all focus group recordings (in Ngoni) are provided, as well as transcripts with translations into both Swahili and English. A translation (into English)of the transcribed interviews is also given. A metadata sheet with anonymised participants is attached. The metadata consists among other of age, sex, educational level and profession. Additionally, information about the participants' bilingualism, as well as their self-estimation of proficiency in Swahili is given.

File names: The metadata numbering of participants is also found in the file naming: The last number of each interview file refers to a numbered participant. The initial naming of the file refers to the type of file: FOC= Focus group (sound file). The file name is followed by date of recording and type of group INT= Interview (sound file). The file name is followed by date of recording and number of anonymised participant ZILPAHFOC = Transcribed and translated focus group discussions (Ngoni, Swahili, English), followed by date of recording and type of group TRANSINT= Transcribed and translated interviews (English), followed by date of recording and number of anonymised participant TRANSFOC=Focus group transcriptions (Ngoni), followed by date of recording and type of group.

Datamaterialet består av 36 ljudinspelningar med totalt 27 informanter/deltagare som alla är tvåspråkiga ngoni från två byar utanför Songea i Ruvumaregionen i Tanzania. Detta ljudmaterial består av 9 fokusgruppdiskussioner och 27 intervjuer med deltagarna. Alla medverkande har givit sitt tillstånd till att materialet kan användas för forskningsändamål.
Fokusgruppinspelningarna är totalt ca 6 timmar. Varje deltagare i dessa fokusgrupperna har dessutom intervjuats enskild efter fokusgruppinspelningen. Alla fokusgruppinspelningarna är transkriberade och sedan översatta till swahili och engelska. Kodväxling till swahili är markerad med fetstil i transkriptioner och översättningar. Intervjuerna genomfördes på swahili, ibland med inslag av ngoni om informanterna behövde det för att förstå. Den engelska översättningen av intervjuerna finns i datasetet, samt ljudinspelningen.
Projektets syfte var att studera varför människor i Ruvuma-regionen i sydvästra Tanzania kodväxlar, dvs alternerar mellan två koder, swahili och ngoni, som är modersmål för de flesta som bor i området. En huvudfråga var om växlingen mellan ngoni och swahili är ett uttryck för att talare av ngoni inte längre kan uttrycka sig tillräckligt bra på sitt modersmål eller om deras kodväxling signalerar något annat. Kan det exempelvis vara ett sätt att uttrycka gruppidentitet - eller rent av flera identiteter samtidigt? Inom ramen för projektet låg fokus på hur ngoni-talare kodväxlar och om det i språksituationen finns processer som bidrar till bevarandet av modersmålet och om hur ngonitalarens attityder påverkar språkanvändning.
I inspelningarna talat ngoni , de flesta självhushållsbönde, på ngoni om kulturarv och förändringar. Teman som diskuteras är bl. a ritualer, regler och traditioner, samt namngivning.

Datamaterialet består av 36 ljudinspelningar med totalt 27 informanter/deltagare som alla är tvåspråkiga ngoni (ngoni-swahili) från två byar utanför Songea i Ruvumaregionen i Tanzania, Mhepai och Peramiho B. Detta ljudmaterial består av 9 fokusgruppdiskussioner och 27 intervjuer med deltagarna i fokusgruppsamtalen. Alla medverkande har givit sitt tillstånd till att materialet kan användas för forskningsändamål.
Fokusgruppinspelningarna utgör totalt ca 6 timmar. De 9 fokusgrupperna bestod av: 15 unga mellan 15-20 år (6 unga män och 3 unga kvinnor från Peramiho B samt 3 unga män och 3 unga kvinnor från Mhepai, och 12 personer äldre än 60år (3 äldre kvinnor och tre äldre män från varje by).

Varje deltagare i dessa fokusgrupper har dessutom intervjuats enskild efter fokusgruppinspelningen. Alla fokusgruppinspelningarna är transkriberade och sedan översatta till swahili och engelska. Kodväxling till swahili är markerad med fetstil i transkriptioner och översättningar. Intervjuerna genomfördes på swahili, ibland med inslag av ngoni om informanterna behövde det för att förstå. Den engelska översättningen av intervjuerna finns i datasetet, samt ljudinspelningen. Inspelningarna gjordes in augusti-september 2014.
En Excel-fil med anonymiserad metadata om deltagarna finns med, bl. a med uppgifter om deltagarnas ålder, kön, utbildning och yrke. I tillägg finns information om deltagarens tvåspråkighet, och färdighet i swahili, baserat på självvärdering.

Syfte:

Datamaterialet består av 36 ljudinspelningar med totalt 27 informanter/deltagare som alla är tvåspråkiga ngoni från två byar utanför Songea i Ruvumaregionen i Tanzania. Detta ljudmaterial består av 9 fokusgruppdiskussioner och 27 intervjuer med deltagarna. Alla medverkande har givit sitt tillstånd till att materialet kan användas för forskningsändamål.
Fokusgruppinspelningarna är totalt ca 6 timmar. Varje deltagare i dessa fokusgrupperna har dessutom intervjuats enskild efter fokusgruppinspelningen. Alla fokusgruppinspelningarna är transkriberade och sedan översatta till swahili och engelska. Kodväxling till swahili är markerad med fetstil i transkriptioner och översättningar. Intervjuerna genomfördes på swahili, ibland med inslag av ngoni om informanterna behövde det för att förstå. Den engelska översättningen av intervjuerna finns i datasetet, samt ljudinspelningen.
Projektets syfte var att studera varför människor i Ruvuma-regionen i sydvästra Tanzania kodväxlar, dvs alternerar mellan två koder, swahili och ngoni, som är modersmål för de flesta som bor i området. En huvudfråga var om växlingen mellan ngoni och swahili är ett uttryck för att talare av ngoni inte längre kan uttrycka sig tillräckligt bra på sitt modersmål eller om deras kodväxling signalerar något annat. Kan det exempelvis vara ett sätt att uttrycka gruppidentitet - eller rent av flera identiteter samtidigt? Inom ramen för projektet låg fokus på hur ngoni-talare kodväxlar och om det i språksituationen finns processer som bidrar till bevarandet av modersmålet och om hur ngonitalarens attityder påverkar språkanvändning.
I inspelningarna talat ngoni , de flesta självhushållsbönde, på ngoni om kulturarv och förändringar. Teman som diskuteras är bl. a ritualer, regler och traditioner, samt namngivning.

Datamaterialet består av 36 ljudinspelningar med totalt 27 informanter/deltagare som alla är tvåspråkiga ngoni (ngoni-swahili) från två byar utanför Songea i Ruvumaregionen i Tanzania, Mhepai och Peramiho B. Detta ljudmaterial består av 9 fokusgruppdiskussioner och 27 intervjuer med deltagarna i fokusgruppsamtalen. Alla medverkande har givit sitt tillstånd till att materialet kan användas för forskningsändamål.
Fokusgruppinspelningarna utgör totalt ca 6 timmar. De 9 fokusgrupperna bestod av: 15 unga mellan 15-20 år (6 unga män och 3 unga kvinnor från Peramiho B samt 3 unga män och 3 unga kvinnor från Mhepai, och 12 personer äldre än 60år (3 äldre kvinnor och tre äldre män från varje by).

Varje deltagare i dessa fokusgrupper har dessutom intervjuats enskild efter fokusgruppinspelningen. Alla fokusgruppinspelningarna är transkriberade och sedan översatta till swahili och engelska. Kodväxling till swahili är markerad med fetstil i transkriptioner och översättningar. Intervjuerna genomfördes på swahili, ibland med inslag av ngoni om informanterna behövde det för att förstå. Den engelska översättningen av intervjuerna finns i datasetet, samt ljudinspelningen. Inspelningarna gjordes in augusti-september 2014.
En Excel-fil med anonymiserad metadata om deltagarna finns med, bl. a med uppgifter om deltagarnas ålder, kön, utbildning och yrke. I tillägg finns information om deltagarens tvåspråkighet, och färdighet i swahili, baserat på självvärdering.

Se beskrivning på den engelska sidan.
Språkligt utanförskap - identitetens betydelse i ett utvecklingsperspektiv - Inspelningar och översättningar (engelska) av intervjuer på swahili
Keywords: identity; identitet; Attitude; Attityd; Interviews as Topic; Intervjuer som ämne; Names; Namn; Taboo; Tabu; Tanzania; Tanzania; Focus Groups; Fokusgrupper; Bantu languages; bantuspråk; language documentation; språkdokumentation; endangered languages; hotade språk; Swahili; swahili; code-switching; kodväxling; Ngoni; ngoni; Cultural and national identity; Kulturell och nationell identitet; Social change; Social förändring; Sociology (Excluding Social Work, Social Anthropology, Demography and Criminology); Sociologi (exklusive socialt arbete, socialantropologi, demografi och kriminologi); Languages and Literature; Språk och litteratur; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; Studies of Specific Languages; Studier av enskilda språk